Pembudayaan Kesetaraan Gender Pada Anak Usia Dini Di Taman Kanak-Kanak - Andini, Andini; Pajarianto, Hadi; Ulpi, Wahyuni (Jurnal Serambi Ilmu, 2026)
This study aims to evaluate the cultivation of gender equality education in early childhood at the Aisyiyah Bustanul Athfal Kindergarten (TK ABA) in Palopo City. The research approach is qualitative with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. The data analysis process consists of three main stages: reduction, presentation, and interpretation of data. To ensure the validity of the data, information triangulation techniques were used by comparing data from various sources. The research results indicate that gender equality has been promoted through various learning strategies that provide equal opportunities for boys and girls. Teachers encourage equal participation among children without limiting their roles based on gender stereotypes. This practice has a positive impact on children's social and emotional development, such as increased self-confidence, cooperation, and mutual respect. However, the process of promoting gender equality still faces obstacles, such as limited teacher training, gender-biased learning media, and the strong influence of local culture. Therefore, the promotion of gender equality from an early age needs to be carried out consistently and collaboratively in order to create a fair, inclusive, and sustainable learning environment.